Study of Mobile City Application in Indonesia - Alifia Nada Putri Galuh; Rini Rachmawati (TATALOKA, 2021)
The Implementation of e-government has been established with the Instruction of President. Application of e-government is a research topic that has received a lot attention because of its improve the function and management of the city by utilizing Information and Communication Technology to improve the quality of public services. In this research focused on one application of e-government that called Mobile City. This study observe 22 application that has been implemented in 22 regencies/cities. This study have goals to identify and compare all 22 Mobile City Applocation to get the rank of the regency/city based on the quality of its application and research city with the best application . The results of the study to show the Mobile City application applies a Location Based Services (LBS) system so the main features of this application showed tourism locations or public facilities. The difference of application features between regencies/cities is depends on how the regency/city developed their application. The city that has the most complete features on its mobile city is Surakarta that called Solo Destination. This application is managed by the Office of Infromation Communication Statistics and Coding of Surakarta City with the most frequently used feature is community complaints.